(untitled) (Boston, MA., 2001)
Using primary and secondary source material and numerous photographs and illustrations, The American Record presents history through a broad perspective. Blending the traditional approach to American history (centered on politics, economics, diplomacy, and war) with the modern approach (including histories of women and children, people of color, and the poor and economically marginal), it offers a version of our national past that is inclusive, complex, and dynamic. Volume 1 covers the span from the European conquest of America through Reconstruction; Volume 2 covers Reconstruction to the present..